Menstrual Hygiene Awareness and Practice Among School Going Girls in Tulsipur Sub-Metropolitan City of Dang - Lahare, Sabitra (Journal of Rapti Babai Campus, 2026)
Menstruation is a normal physiological process occurring in adolescent girls where by uterus sheds its blood and tissue through the vagina. Menstrual hygiene includes adolescent girls using hygienic menstrual management materials to absorb the flow, privacy for changing pad, soap and water to wash the body and access to facilities where used absorbent can be disposed of safely. This study aimed to find awareness and practice on menstrual hygiene among schoolgirls in an urban municipality. A descriptive cross-sectional study was conducted with multistage sampling method among the government schools of Tulsipur Sub Metropolitan city, Dang Nepal. Self-administered structure questionnaires were used to collect data from 327 school going girls of SSC level (Grade 8,9 and 10). The tool was confirmed by I-CVI and S-CVI (0.93) for awareness and practices (0.88). Descriptive and inferential statistics were used for data analysis in the SPSS 26. Average age of participants was age 14.70±1.21 years old. Majority (86.2 %) of the girls had good knowledge about menstrual hygiene with their mothers as predominant source of information (92.7 %). Nearly universal (95.4%) of the respondents practiced in the line of menstrual hygiene. Two third (66.4%) of the participants used both disposable pad and clean cloth pad while 28.3 percent used only disposable sanitary pad during their menstruation.